2002
DOI: 10.1124/jpet.102.032797
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Mechanisms of Neurogenic Inflammation

Abstract: Since the initial observations that stimulation of sensory neurons produces vasodilation, plasma extravasation, and hypersensitivity, much progress has been made in understanding the etiology of neurogenic inflammation. Studies have focused largely on the role of the neuropeptides, substance P and calcitonin gene-related peptide, which are released in the periphery by activation of small diameter sensory neurons. Recent work, however, has begun to emphasize the cellular mechanisms involved in regulating the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
284
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 431 publications
(293 citation statements)
references
References 56 publications
4
284
0
1
Order By: Relevance
“…The family of neurokinin receptors NK 1 , NK 2 and NK 3 are G-protein coupled receptors which activate phospholipase C (Maggi, 1995(Maggi, ,1997b. The breakdown of phospholipids into diacylglycerol by PLC, activates PKC (Torrens et al, 1997) to phosphorylate and inhibit a number of K + channels (Boland and Jackson, 1999,Hagiwara et al, 2003,Richardson and Vasko, 2002. We have shown that direct activation of PKC with PDBu did not increase firing in DRG neurons.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The family of neurokinin receptors NK 1 , NK 2 and NK 3 are G-protein coupled receptors which activate phospholipase C (Maggi, 1995(Maggi, ,1997b. The breakdown of phospholipids into diacylglycerol by PLC, activates PKC (Torrens et al, 1997) to phosphorylate and inhibit a number of K + channels (Boland and Jackson, 1999,Hagiwara et al, 2003,Richardson and Vasko, 2002. We have shown that direct activation of PKC with PDBu did not increase firing in DRG neurons.…”
Section: Discussionmentioning
confidence: 81%
“…There is growing evidence that neurokinin auto-receptors influence the properties of C-R nociceptive neurons (Hu et al, 1997,Maggi, 1997b,Richardson and Vasko, 2002. In the urinary bladder, neurokinin A released from sensory nerves seems to be involved in both the normal voiding function induced by bladder distension as well as the hyperactive voiding induced by noxious stimuli (Morrison et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The local anaesthetic agents in EMLA cream block axon reflexes (Morris and Shore, 1996), and could also prevent intraneural prostaglandin formation (Richardson and Vasko, 2002). Sorbolene pretreatment also inhibited the local vasodilator response to phenylephrine, but not the axon reflex.…”
Section: Discussionmentioning
confidence: 99%
“…The flare is 4 thought to be mediated by neural discharge that spreads retrogradely through the terminal network of mechano-insensitive nociceptive C-fibres (termed an axon reflex), ultimately releasing neuropeptides that act on mast cells, immune cells and vascular smooth muscle to increase local blood flow (Schmelz et al, 2000;Schmelz and Petersen, 2001;Richardson and Vasko, 2002). Intradermal administration of noradrenaline by microdialysis on the dorsal aspect of the human hand did not induce axon reflex vasodilatation (Zahn et al, 2004).…”
mentioning
confidence: 99%
“…The released substances produce a myriad of autocrine or paracrine effects on endothelial, epithelial, and resident immune cells (Langerhans), which lead to arteriolar vasodilatation ("flare," via CGRP) and/or increased vascular permeability and plasma extravasation from venules (edema, via substance P). Liberated enzymes (e.g., kallikreins) and blood cells (e.g., platelets, mast cells) further contribute to the accumulation of inflammatory mediators and neurogenic inflammation (110,111). A large variety of substances feed back onto nociceptors innervating the injured region and sensitize peripheral terminals by direct and indirect actions at ion channels, receptors, and second messenger cascades (87,102,111,112).…”
Section: Adaptive and Maladaptive Shifts In Pain Thresholdmentioning
confidence: 99%